Non-English Department Students’ Understanding of Cultural Concepts Expressed in Indonesian Folklore through Focus Group Discussion - Wahyuni, Sri; Budiman, Muhammad Arief (Universitas Stikubank (UNISBANK) Semarang, 2024)
Teaching English to non-English department students must consider many aspects of the language. It is important to not only teach them how to understand grammar but also to understand literary work. Some lecturers sometimes ignore teaching the students to make use the literary works especially to teach cultural concepts to students. They mostly focused on the students' need to understand text in the context of their major only. The purpose of this research is to know to what extent the mathematics students in 2022/2023 understand the cultural context in Indonesian folklore. The method applied in this research is descriptive analysis. Focus group discussion in this research is used to help the students understand through sharing ideas in groups to analyze the literary works. Through this Focus Group Discussion, students understanding of the cultural concept of Indonesian folklore can be improved through sharing ideas. In the end, it is hoped that while the students learn the language they also learn about Indonesian literary work. Keywords: culture, literary work, focus group discussion